Contabilidad de costos en los negocios artesanales de Usiacurí Atlántico (2021)
In any business, organization or economic entity, accounting is essential for its implementation. There are multiple theoretical bases where companies take as a base those that best suit their needs, as well as accounting diversity, some obligations such as financial accounting, and others that require many needs depending on their characteristics, management accounting, for example. This study is especially focused on cost accounting, whose general objective is to describe the cost accounting processes implemented by artisans from the municipality of Usiacurí in the Atlantic department, being this one of the richest in creative crafts in Colombia, and which is pioneer in crafts with Palma de iraca, Sabanalarga and Baranoa. This study has an empirical-inductive epistemological approach, where the surveys of artisans in this sector of the Atlantic are analyzed empirically, the chosen sample is represented by nine (9) of the most relevant producers in production size and load in the municipality of Usiacurí. Finally, relevant findings were obtained such as: The target population, evidence of shortcomings and care in the cost classification criteria, and, therefore, this generates uncertainty for the allocation of costs of the production and accumulation processes, to such an extent, where a very considerable percentage of the population, without costing mechanisms, and the degree of control existing from the implementation of classification criteria and cost allocation, is significantly nil.